Allogeneic Hematopoietic Cell Transplantation in Patients aged 50 years or older with Severe Aplastic Anemia - Rice, C (Biol Blood Marrow Transplant, 2018)
We report on 499 patients with severe aplastic anemia aged ≥50 years who underwent hematopoietic cell transplantation (HCT) from HLA-matched sibling (n=275), or HLA-matched (8/8) unrelated donors (n=39187) between 2005 and 2016. The median age at HCT was 57.8 years; 16% of patients were 65–77 years old. Multivariable analysis confirmed higher mortality risks for patients with performance score less than 90% (HR 1.41 (1.03–1.92), p=0.03) and after unrelated donor transplantation (HR 1.47 (1–2.16), p=0.05). The 3-year probabilities of survival for patients with performance score 90–100 and less than 90 after HLA-matched sibling transplant were 66% (57–75%) and 57% (47–76%), respectively. The corresponding probabilities after HLA-matched unrelated donor transplantation were 57% (48–67%) and 48% (36–59%). Age at transplantation was not associated with survival but grade II-IV acute GVHD risks were higher for patients aged 65 years or older (sHR 1.7 (1.07–2.72), p=0.026). Chronic GVHD was lower with GVHD prophylaxis regimens calcineurin inhibitor (CNI) + methotrexate (sHR 0.52 (0.33–0.81), p=0.004) and CNI alone or other agents (sHR 0.27 (0.14–0.53), p<0.001) compared to CNI + mycophenolate. While donor availability is modifiable only to a limited extent, choice of GVHD prophylaxis and selection of patients with good performance scores are key for improved outcomes.